Perbedaan Tingkat Kepuasan antara Pasien Pengguna BPJS Kesehatan dengan KLU Sehat - Nova Budiharjo; Saimi Saimi; Menap Menap; Sismulyanto Sismulyanto; Ovie Lestya Nurdiana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the difference in the level of satisfaction of BPJS health patients and KLU Sehat patients with inpatient services at the North Lombok District Hospital. The research method used is cross-sectional research. The results showed that the community satisfaction index of BPJS patients was included in the satisfied category. In contrast, the community satisfaction index of KLU Sehat patients was included in the reasonably satisfying category. This study found differences in the level of satisfaction of BPJS Health patients and KLU Sehat patients in the inpatient room at the North Lombok District Hospital. In conclusion, BPJS patient satisfaction is higher when compared to KLU Sehat patient satisfaction. Keywords: BPJS, Health Insurance, Satisfaction